Persepsi Petani Terhadap Financial Technology Untuk Mendukung Kemandirian Petani - Eny Ivan’s; Diky Angga Hendrawan (lembaga penelitian universitas swadaya gunung jati, 2024)
The development of information and communication technology stimulates the development of financial techhnology (fintech). However, the role of fintech in supporting the progress of the agricultural sector has not been easily adapted by farmers, especially rural farmers. Narrow land ownership does not allow farmers to expand the scale of their business through extensification and intensification. Fintech in the form of offering financing should be a solution for farmers to advance their farming business. Data analysis techniques were carried out qualitatively to test farmer’s perceptions in adopting fintech. The research results show that farmer’s perceptions of fintech are seen from farmer’s knowledge of the definition of fintech, 54,90% agree; from knowledge of the benefits and advantages of fintech, 57,35% agreed and from knowledge of types of fintech, 50% agreed. There is a positive and significant relationship between farmers’ perceptions of fintech and the level of fintech adoption with the nature of the relationship being moderate.Keywords: Adoption, Fintech, Perception, Farmers